2021
DOI: 10.3390/life11121348
|View full text |Cite
|
Sign up to set email alerts
|

Use of Biological Treatments in Elderly Patients with Skin Psoriasis in the Real World

Abstract: Biological drugs have prompted a revolution in the treatment of patients with psoriasis because of their favourable efficacy/risk profile. The aims of our study are to determine whether there is any difference in the pattern of use of biological treatments for older (65+ years) and younger patients diagnosed with plaque psoriasis by the Dermatology Service of the Hospital Universitario de Asturias (HUCA), to understand the survival of these drugs, and to identify the factors that predict the discontinuation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 50 publications
2
7
0
Order By: Relevance
“…Drug survival is a widely used measure that combines several aspects of treatment modalities (e.g., effectiveness and safety) [ 17 19 ]; however, literature on drug survival in older patients with psoriasis is sparse. We found a comparable overall drug survival between the age groups, before and after correction for confounding factors, as also reported for a period of 2 years by Osuna et al [ 20 ]. The crude and confounder-corrected drug survival with regard to ineffectiveness was lower for patients aged ≥ 65 years.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Drug survival is a widely used measure that combines several aspects of treatment modalities (e.g., effectiveness and safety) [ 17 19 ]; however, literature on drug survival in older patients with psoriasis is sparse. We found a comparable overall drug survival between the age groups, before and after correction for confounding factors, as also reported for a period of 2 years by Osuna et al [ 20 ]. The crude and confounder-corrected drug survival with regard to ineffectiveness was lower for patients aged ≥ 65 years.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, studies describing drug survival in this population are lacking. Our study is an addition to the current scarce body of evidence in older patients; however, more evidence regarding older patients with psoriasis is being published [ 20 , 36 38 ]. A strength of this study is its high external validity, due to its real-world practice nature, and multicenter, prospective design.…”
Section: Discussionmentioning
confidence: 99%
“…Authors also investigated drug survival, and they found that it did not differ among the three studied drugs. These data are also confirmed by Osuna et al The authors compared drug survival in elderly and younger patients and did not find differences related to the age of the patients [ 58 ].…”
Section: Therapeutic Management Of Elderly Patients With Moderate-to-...supporting
confidence: 73%
“…They include etanercept, adalimumab, infliximab, and certolizumab pegol either as originator or biosimilar drugs, when available. Generally, a similar efficacy in elderly patients undergoing anti-TNF has been reported so far when compared with younger patients [ 55 , 56 , 57 , 58 , 59 ], but a few studies show a lower response rate in elderly patients that were treated for other diseases than psoriasis [ 60 ]. A previous retrospective study positively evaluated the long-term efficacy and safety profile of etanercept and adalimumab in the treatment of elderly patients affected by plaque-type psoriasis and psoriatic arthritis [ 61 ].…”
Section: Therapeutic Management Of Elderly Patients With Moderate-to-...mentioning
confidence: 69%
“…4 For these reasons, elderly patients with moderate-to-severe psoriasis are often undertreated. [2][3][4][5] Few data are available on the use of interleukin (IL) inhibitors in the elderly, as they are often underrepresented in clinical trials. [3][4][5] This study aimed to evaluate the effectiveness and safety of anti-IL-23 and anti-IL-17 biologics for psoriasis in over-65 patients.We collected data from two Italian hospitals' database records, including patients ≥65 years old receiving an anti-IL-23 or anti-IL-17 agent approved for psoriasis for at least 16 weeks.…”
mentioning
confidence: 99%